Derrida and the contradiction of the Gift - Santana, Wellington José (Virtualia Journal, 2020)
The present article grapples a critical analysis of the philosophical query about the gift raised by Marcel Mauss and implemented by Jacques Derrida. A gift as such can never be given and has an internal contradiction that forces it towards annihilation, cancelling it when in the very moment it’s acknowledged. Therefore the article analyzes the condition of possibility of the gift as well as the condition of impossibility. Despite of being a paradox, we shall ask why the philosophical approach of the gift ends up being a burden for the common sense. Key words: Gift, paradox, Derrida, common sense Resumo O presente artigo busca fazer uma análise crítica sobre a questão filosófica do dom iniciado pelo sociólogo francês Marcel Mauss e posteriormente implementado por Jacques Derrida. O dom, segundo Derrida, nunca pode ser dado e encerra uma contradição interna que o força para o nada, cancelando-o no momento em que é reconhecido como tal. O artigo analisa as condições de possibilidade e impossibilidade do dom. Apesar de ser um paradoxo, analisar-se-á por que um cuidadoso exame filosófico do dom acaba por torná-lo um pesadelo para o seu significado no senso comum. Palavras chave: Dom, paradoxo, Derrida, senso comum